Relationship between indole production and differentiation of Klebsiella species: indole-positive and -negative isolates of Klebsiella determined to be clonal. - Maslow, J N (1993)
Klebsiellae are an important cause of nosocomial infections. The two clinically relevant species, Klebsiella pneumoniae and Klebsiella oxytoca, are differentiated by the ability to produce indole from tryptophan, K. oxytoca being indole positive. We report here the detailed biochemical and molecular analysis of two isolates of Klebsiella, cultured from the same urine specimen, that differed only in their ability to produce indole. The two isolates were identical as determined by ribotyping and pulsed-field gel electrophoresis, and they differed from 10 epidemiologically unrelated strains. Probing with the Escherichia coli tryptophanase operon, tna, revealed seven restriction fragment length polymorphisms (RFLP) among the 12 strains. The two index strains had identical RFLP; no single RFLP could account for all of the indole-positive or -negative strains. Thus, the identification of epidemiologically related strains of Klebsiella differing only in indole production may warrant further examination to determine whether the strains are clonal.